Cultural Tourism Development at Chin Swee Caves Temple, Genting Highlands: A GIS and SWOT-Based Learning Resource - Ratu Insani Ramadona; Dedi Hermon; Rosmadi Bin Fauzi; Daniel Friess; Ratu Insani Ramadona; Dedi Hermon; Rosmadi Bin Fauzi; Daniel Friess (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Cultural tourism development plays an important role in maintaining destination sustainability amid the dominance of modern entertainment tourism. Chin Swee Caves Temple in the Genting Highlands, Malaysia, represents a cultural and spiritual tourism destination characterized by distinctive architectural, historical, and religious values and has potential as a contextual learning resource. Previous studies on Genting Highlands have largely focused on entertainment tourism and economic development, while limited attention has been given to the integration of cultural tourism, spatial analysis, and educational functions. This study aims to analyze cultural tourism potential, identify GIS-based cultural tourism zoning, and formulate development strategies using SWOT analysis integrated with the educational role of the site. The research employed a mixed-method approach combining field observations, interviews, and documentation with spatial analysis using Geographic Information Systems (GIS). Internal and external factors influencing tourism development were evaluated using IFAS and EFAS matrices. The findings show that Chin Swee Caves Temple is positioned in Quadrant I, indicating a growth-oriented strategy supported by strong internal factors and favorable external opportunities. Key strengths include accessibility, environmental comfort, strategic location, and the aesthetic and spiritual value of traditional Chinese architecture, while the main challenges relate to limited cultural interpretation, visitor safety management, local community involvement, and competition with modern tourism attractions. The novelty of this study lies in integrating GIS-based spatial zoning with SWOT strategic analysis to support cultural tourism development while positioning the site as a contextual learning resource for geography and social studies education.